Bath Ankylosing Spondylitis Disease Activity Index is Associated With the Quality of Sleep in Ankylosing Spondylitis Patients - Song, Byung Wook; Jeong, Hye-Jin; Kim, Bo Young; Cho, Yong Won; Son, Chang-Nam; Kim, Sung-Soo; Kim, Sang-Hyon (Journal of rheumatic diseases, 2021)
High disease activity of ankylosing spondylitis (AS) is associated with poor sleep quality The purpose of this study was to identify which of the representative tools for evaluating the disease activity of AS best reflect the quality of sleep. A total of 107 AS patients were enrolled in the study and the sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI) Age, sex, concomitant medication, erythrocyte sedimentation rate (ESR), serum C-reactive protein (CRP) level, Beck Depression Inventory second edition (BDI-II), Bath ankylosing spondylitis disease activity index (BASDAI), ankylosing spondylitis disease activity score (ASDAS)-ESR, ASDAS-CRP, pain visual analog scale, Insomnia Severity Index (ISI), and Epworth Sleepiness Scale (ESS) were analyzed as covariates. Overall, 65% (70/107) of subjects reported poor sleep quality (PSQI>5) There was a positive correlation between the sleep quality and disease activity as measured by the BASDAI, ASDAS-ESR, and ASDAS-CRP In addition, the BASDAI demonstrated good correlations with ISI, ESS, and BDI-II, respectively However, only BASDAI showed reliable correlation with PSQI among the disease activity parameters of AS (adjusted odd ratio 5.36, p=0.023). BASDAI is the most reliable parameter of disease activity associated with the sleep quality in patients with AS.